A Review on Mitigating Disruptions and Improving Resilience in Supply Chain Logistics - Al-Qasimi M.; Khudari M.; Al Balushi Z. (World Scientific and Engineering Academy and Society, 2025)
Businesses need resilience in supply chain logistics to efficiently manage and minimize disruptions and maintain a smooth flow of goods and services. The present study aims to examine the elements influencing supply chain resilience to enhance overall supply chain performance. A thorough literature assessment served as the foundation for the study's methodology. Two methods were employed to examine the body of knowledge on supply chain resilience: first, databases and journals were searched using specific keywords; second, the publications' references were followed to find the literature that the databases and journals had not been able to locate. When building the sample for this analysis, only publications released after 2002 were included. This strategy provided 150 high-quality research articles that served as the basis for the literature evaluation reported in this study. The research article's conclusions state that manufacturers or businesses need to consider both internal and external factors when identifying and analyzing potential supply chain interruptions. To handle hazards that have been discovered, develop a comprehensive risk management plan and rank hazards according to likelihood and possible consequences. This information could prove vital for managers and supply chain experts in manufacturing companies with useful information that helps them improve the robustness of their supply networks. Moreover, because this study highlights the connection between supply chain resilience and an organization's overall performance, it occupies a significant position in the literature. The findings suggest that a company's reputation among supply chain partners and consumers is negatively impacted by frequent interruptions to business. This finding is consistent with the crisis literature, as stated by Coombs, which shows that a firm's reputation suffers more when it bears a larger portion of the blame for a crisis. The study emphasizes strategies for supply chain resilience, including diversifying suppliers, implementing robust risk management, enhancing transparency, investing in advanced technologies, fostering collaboration, and ensuring agility and flexibility in unforeseen disruptions. ? 2024, World Scientific and Engineering Academy and Society. All rights reserved.